PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE INDEX CARD MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD MUHAMMADIYAH 6 PEKANBARU - Dahnia Putri; Syahrilfuddin Syahrilfuddin; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak: Problem in this study is the low learning outcomes of IPS students class V SD Muhammadiyah 6 Pekanbaru caused by teachers still apply the method of lecture to the end of learning, teachers do not use appropriate learning models, teachers do not use instructional media, teachers do not actively involve students so there is less interaction between teachers and students. For that need to be improved through the application of cooperative learning model type index card match. This research includes a classroom action research conducted for 2 months, namely October-November 2017 with two cycles.Each cycle consists of two meetings of learning activities and one daily test. The subjects of the study were the students of VA SD Muhammadiyah 6 Pekanbaru with 22 students. The instrument of data collection used is observation sheet of teacher and student activity and item on learning result test. This test consists of 20 objective questions for each cycle. The results showed that the average score of the students' basic score is 68.41 increase in the first cycle to 78.41 then increased again to 86.82 in cycle I. Increase learning outcomes that happen from the basic score to UH I that is 14.62% and the score UH II to 26.91%. The results show that the implementation of cooperative learning model of index card type match can improve learning outcomes of IPS students of grade V SD Muhammadiyah 6 Pekanbaru.Keywords : Cooperative Learning Model Index Card Match Type, Learning Results IPS